The Aromatic Ring of Phenylalanine 334 Is Essential for Oligomerization of Vibrio vulnificus Hemolysin - Kashimoto, Takashige (American Society for Microbiology (ASM), 2010)
Vibrio vulnificus hemolysin (VVH) is thought to be a member of the cholesterol-dependent cytolysin (CDC) family of pore-forming toxins. To date, the structure-function relationships of CDCs produced by Gram-negative bacteria remain largely unknown. We show here that the aromatic ring of phenylalanine residue conserved in Vibrionaceae hemolysins is essential for oligomerization of VVH. We generated the VVH mutants; substituted Phe 334 for Ile (F334I), Ala (F334A), Tyr (F334Y), or Trp (F334W); and tested their binding and oligomerizing activity on Chinese hamster ovary cells. Binding in all mutants fell by approximately 50% compared with that in the wild type. Oligomerizing activities were completely eliminated in F334I and F334A mutants, whereas this ability was partially retained in F334Y and F334W mutants. These findings indicate that both hydrophobicity and an aromatic ring residue at the 334th position were needed for full binding activity and that the oligomerizing activity of this toxin was dependent on the existence of an aromatic ring residue at the 334th position. Our findings might help further understanding of the structure-and-function relationships in Vibrionaceae hemolysins.